2022
DOI: 10.1002/admi.202270178
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam as Straightener to De‐Wrinkle Large 2D Black Phosphorus Flake: An In Situ TEM Monitoring (Adv. Mater. Interfaces 32/2022)

Abstract: In article number 2201320, Manpreet Kaur, Kiran S. Hazra, and colleagues report on electron beam based straightening of 2D materials, a step towards their practicality for next generation electronics. In-situ TEM monitoring demonstrates flattening of 2D layers is synchronous with the de-stressing of lattice under e-beam irradiation, and the declination-ridden lattice can be evolved into the uniformly spaced parallel lattice planes in a controlled manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Kaur et al demonstrated a straightening method to smoothen and de-wrinkle of 2D BP flakes via electron beam irradiation to improve crystallinity and remove line defects from the lattice. [143] The ironing of BP using electron beam irradiation enabled to control the stress in lattice and the buckling structure of the flake, which can be an important moving forward for controlling 2D atomic nanostructure. Another novel way to enhance optoelectronic properties for PD applications is using hybrid heterostructures.…”
Section: Bpmentioning
confidence: 99%
“…Kaur et al demonstrated a straightening method to smoothen and de-wrinkle of 2D BP flakes via electron beam irradiation to improve crystallinity and remove line defects from the lattice. [143] The ironing of BP using electron beam irradiation enabled to control the stress in lattice and the buckling structure of the flake, which can be an important moving forward for controlling 2D atomic nanostructure. Another novel way to enhance optoelectronic properties for PD applications is using hybrid heterostructures.…”
Section: Bpmentioning
confidence: 99%